Community-based heat adaptation interventions for improving heat literacy, behaviours, and health outcomes: a systematic review - Johar, Hamimatunnisa; Abdulsalam, Fatima Ibrahim; Guo, Yuming; Bärnighausen, Till; Jahan, Nowrozy Kamar; Watterson, Jessica; Leder, Karin; Gouwanda, Darwin; Letchuman Ramanathan, G R; Lee, Kenneth Kwing Chin; Mohamed, Norlen; Zakaria, Thahirahtul Asma'; et al. (The lancet. Planetary health, 2025)
Anthropogenic climate change, resulting in a continuous rise of global temperature, has detrimental effects on human health, particularly among vulnerable populations, such as individuals with low income, older adults, and people with pre-existing health conditions. To reduce the heat-related health consequences, effective interventions targeting community members, especially vulnerable populations, are paramount. This systematic review aims to identify and evaluate the effectiveness of community-based heat adaptation behavioural interventions aimed at improving heat literacy, promoting adaptive behaviours, and enhancing health outcomes amid rising global temperatures. In this systematic review, peer-reviewed English-language articles focused on community-based heat adaptation intervention studies published in PubMed, MEDLINE via Ovid, Embase, CINAHL, Scopus, and Web of Science from database inception to Jan 1, 2024, were retrieved and reported according to the PRISMA 2020 guidelines. The quality of the articles was evaluated with the use of a mixed-methods appraisal tool. The analysis synthesised intervention effectiveness across multiple outcome domains measurable at both individual and household levels, identified key factors influencing successful implementation, and highlighted areas for future research. The initial search yielded 1266 articles, of which ten were finally included. The majority of the included studies (n=7) were from high-income countries. Most intervention modules focused on preventive measures during heat exposure, whereas only a few addressed information on disease mechanisms, risk factors, and monitoring environmental changes. Although most studies reported significant improvements in heat literacy and a reduction in heat-related symptoms, the evidence for behavioural changes and health outcomes was mixed. Our review reveals methodological shortcomings, as none of the included studies incorporated heat literacy frameworks, behavioural theory, or participatory approaches to include community input throughout the research. Our findings highlight the need for a comprehensive approach that incorporates frameworks to enhance intervention effectiveness and improve public health resilience amid rising global temperatures. Culturally appropriate community-led interventions and integration of digital tools are promising avenues for increasing uptake of interventions. This study is registered with PROSPERO (CRD42024514188).